Unplugged Coding to Develop Computational and Collaborative Thinking in Early Childhood Education - Oktaviani, Putri; Diana, Diana; Waluyo, Edi; Formen, Ali (Program Studi Magister Pendidikan Anak Usia Dini, 2025)
Integrating computational and collaborative thinking from early childhood is essential in the digital era. This study examined the implementation of Unplugged Coding computer-free programming at the Larasati Early Childhood Education Cluster, with a focus on children’s cognitive and social development. Using a qualitative case study method, data were collected through observation, interviews, and documentation at TK Islam An-Nur Kedungringin. Activities involved grid floor games, number dice, and directional arrows, with teachers acting as facilitators. Results showed that 87.5% of children demonstrated improvement in computational thinking components such as sequencing, pattern recognition, decomposition, and algorithmic reasoning. Moreover, 81.2% of children exhibited enhanced collaborative skills, including turn-taking, group problem-solving, and active communication. Contributing factors included structured planning, engaging learning tools, and a supportive environment. Limitations involved limited infrastructure and varying teacher readiness. The study concludes that Unplugged Coding is an effective, low-tech approach to foster 21st-century skills in early learners and recommends broader implementation supported by teacher training and curriculum integration.